2018
DOI: 10.1038/s41372-018-0185-9
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the classroom: a national pilot curriculum for physiology in neonatal–perinatal medicine

Abstract: Fellows and educators preferred FC learning over traditional didactics and reported that FCs facilitated creation of a learning community, fostering active learning. The favorable response toward this pilot project and the feasibility of its use supports further development of a standardized NPM physiology curriculum for fellowship training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Recognizing the potential benefits of FC learning, the Organization of Neonatal-Perinatal Medicine Training Program Directors (ONTPD) performed a pilot study of an e-learning based FC National Neonatology Curriculum (NNC) at five academic centers. 10 Consistent with previously published studies of FC learning in medicine, the pilot demonstrated that both learners and educators preferred FC learning to traditional didactics. In addition, the FC model promoted the development of a learning community within the learners at each academic center.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Recognizing the potential benefits of FC learning, the Organization of Neonatal-Perinatal Medicine Training Program Directors (ONTPD) performed a pilot study of an e-learning based FC National Neonatology Curriculum (NNC) at five academic centers. 10 Consistent with previously published studies of FC learning in medicine, the pilot demonstrated that both learners and educators preferred FC learning to traditional didactics. In addition, the FC model promoted the development of a learning community within the learners at each academic center.…”
supporting
confidence: 83%
“…The e-learning programs were created by academic NPM faculty with previous training in medical education and were designed to address the American Board of Pediatrics (ABP) NPM respiratory physiology content specifications. 10,11 Respiratory physiology is the largest subsection of the ABP content for NPM and was chosen as the first target of the NNC to best address learners' needs. For each respiratory topic (i.e., respiratory respondents preferred the FC approach to traditional didactics, with fellows showing a greater degree of preference than faculty (68 vs. 52%, respectively, p ¼ 0.04).…”
Section: Methodsmentioning
confidence: 99%
“…which is creating a national, standardized, peer-reviewed physiology curriculum for NPM fellows. 10 The goal of the collaboration is to scaffold the learning provided through the physiology curriculum with simulations covering the same physiology. Future research on the educational impact of a standardized simulation curriculum would be needed to evaluate its impact on knowledge acquisition, knowledge retention, and clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty who participated in those FCs found the educational experience to be an effective, useful, and efficient method to apply learning in a supportive environment. (10) There still remain some mixed results about improved long-term outcomes with use of the FC approach. However, some authors argue that discrepancies in outcomes could be more of a reflection of assessment questions being poorly calibrated to test at high cognitive levels based on Bloom's level of cognition.…”
Section: Educational Research and Analysis Of Fcsmentioning
confidence: 99%
“…The ONTPD NNCC is committed to rigorous educational research to determine the best approach to fellowship education on a national level. Following a successful pilot (10) and roll-out of the respiratory physiology section (11) of the NNC, a randomized controlled trial (RCT) was launched to study the FC approach for NPM fellow physiology education. The NNC RCT aims to compare knowledge acquisition and retention of fellows taught neonatal gastroenterology and bilirubin ABP NPM board content via the FC approach with those taught using a traditional slide-based didactic approach.…”
Section: The Ontpd Nnc Randomized Controlled Trialmentioning
confidence: 99%